Moderation in Infaq (spending) in accordance with Qur'an and Sunnah - Tahir, Ibrahim Nuhu (2015)
Islam is a religion that is based on solidarity, help and corporation among its followers. The Iqtisad of Islam is based on earning and spending halal wealth in the correct manner. Both actions have to be well managed in order to create a sustainable society. Hence it is only appropriate that Infaq is one of the tools that the Qur’an and Sunnah teach as a way to narrow the income gap between the rich and the poor. Numerous examples are found in the Qur’an and Sunnah encouraging Muslims of every income level to share their wealth with the needy. This is contrary to the currently popular materialism that has led the world into a culture of excessiveness in spending and consumption. Subsequently this has increased the amount of debt owed by individuals, business and governments. An alarming trend is that there is minimal concern about attaining wealth through halal means and sources of haram income are on the rise. Consequently there has been a decrease of blessings in wealth and contentment regardless of the magnitude of one’s wealth. On the contrary, moderation is highly encouraged and appreciated by the Shari'ah in all circumstances. This paper addresses the guidelines given by the Qur’an and Sunnah on moderation and its importance in building a sustainable economy and society. It discusses the basis of moderation in infaq which are: faith, wealth, amanah (Trust), believing in accountability in the hereafter, prohibition of all forms of extravagance or excessiveness in all of one’s affairs which Qur’an describes as a form of inspiration from Shaitan. The paper is mainly based on the revealed texts that address the issue directly or indirectly.